Vre Modelling Limitations in Power Systems: The Case of Chile - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2024)
This review presents the state of the art about the modeling of Inverter-Based Resources (IBR s), in the context of bulk power systems with high penetration of Variable Renewable Energy (VRE) and the impact of these resources on the dynamics. The discussion on a precise modeling through EMT or RMS models this new dynamic - be it detailed or reduced - is still open, a consequence of large-magnitude phenomena whose real systemic response has not been able to be satisfactorily represented. © 2024 IEEE.